Europe's debt crisis, coordination failure, and international effects - Stefan Collignon (Asian Development Bank Institute (ADBI), 2012)
This paper gives an overview of the causes of the European debt crisis and the consequences for the external relations. It finds that political mishandling has increased uncertainty, which has contributed to a tendency for the euro to become weaker.
Keywords: E42; F33; F36; G01; 330; europe debt crisis; euro; euro area; Haushaltsdefizit; Öffentliche Schulden; Eurozone; Außenpolitik; Internationale Beziehungen; EU-Staaten